Sustainability Aspects in Water Management Policies in Regional Drinking Water Companies (RDWC) (Public Accounting and Sustainability, 2024)
Research aims: This research aims to provide good policy proposals regarding managing and maintaining water sources carried out by Regional Drinking Water Companies (RDWC) by paying attention to sustainability aspects. Design/Methodology/Approach: The method used in this study was a scoping review. A scoping review can be interpreted as a review to detail the concepts that form the basis of a research domain, the sources of evidence, and the types of evidence available. The data were analyzed using content analysis, a technique used to conclude by finding the characteristics of a message, which was carried out objectively and systematically. Research findings: The research results demonstrated that the passion for preserving the environment and biodiversity has still not explicitly been reflected in regional regulations about RDWC. Theoretical contribution/Originality: This research is expected to contribute to adding literature in the accounting sustainability, environment, and public policy fields. Practitioner/Policy implication: This research suggests that the Ministry of Public Works and Public Housing, the Ministry of Environment and Forestry, the Ministry of Home Affairs, as well as all regional governments in Indonesia, can create and repair policy in the context of providing, managing, and utilizing water resources by taking into account environmental and sustainability issues. Furthermore, RDWC performance evaluators such as Financial and Development Supervisory Agency (BPKP) and Inspectorate are expected to add assessment points related to environmental and sustainability aspects. Research limitation/Implication: There was limited information from overseas water companies, and this study did not highlight all RDWCs in Indonesia.